2012
DOI: 10.1111/j.1365-277x.2012.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with coeliac disease and a gluten‐free diet: a Canadian perspective

Abstract: Objective: Strict adherence to a gluten-free diet is the only treatment for coeliac disease. The gluten-free diet is complex, costly and impacts on all activities involving food, making it difficult to maintain for a lifetime. The purpose of this cross-sectional study was to evaluate the difficulties experienced, the strategies used and the emotional impact of following a glutenfree diet among Canadians with coeliac disease. Methods: A questionnaire was mailed to all members (n = 10 693) of both the Canadian C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
142
2
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(175 citation statements)
references
References 45 publications
12
142
2
13
Order By: Relevance
“…The proportion of CD between the genders is two women to one man (22) . However, in this study, it was necessary to remove the statistical analysis of the data provided by men because of their low adhesion to the research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of CD between the genders is two women to one man (22) . However, in this study, it was necessary to remove the statistical analysis of the data provided by men because of their low adhesion to the research.…”
Section: Discussionmentioning
confidence: 99%
“…It also evaluate how the needs and expectations of patients are affected by their condition. From this perspective, some authors investigated the impact of CD, and also the GFD, on patients lives (4,22) . However, no studies on the topic were found in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is especially important in newly diagnosed patients as it can positively change a patient's approach to a new dietary regime. In consequence, it can prevent the development of various health complications caused by even the smallest amount of gluten [12].…”
Section: Patient Support and Education-key To Successmentioning
confidence: 99%
“…Several authors described difficulties to follow a strict GFD and indicate factors as taste, scarcity, cost and insufficient labeling of products. Also, the difficulty in eating out and limited knowledge of general community contribute to a negative impact on quality of life patients leading to low compliance, particularly in adolescence [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%